Updated and enhanced pig cardiac transcriptome based on long-read RNA sequencing and proteomics - Müller, Torsten; Boileau, Etienne; Talyan, Sweta; Kehr, Dorothea; Varadi, Karl; Busch, Martin; Most, Patrick; Krijgsveld, Jeroen; Dieterich, Christoph (Journal of molecular and cellular cardiology, 2021)
Clinically translatable large animal models have become indispensable for cardiovascular research, clinically relevant proof of concept studies and for novel therapeutic interventions. In particular, the pig has emerged as an essential cardiovascular disease model, because its heart, circulatory system, and blood supply are anatomically and functionally similar to that of humans. Currently, molecular and omics-based studies in the pig are hampered by the incompleteness of the genome and the lack of diversity of the corresponding transcriptome annotation. Here, we employed Nanopore long-read sequencing and in-depth proteomics on top of Illumina RNA-seq to enhance the pig cardiac transcriptome annotation. We assembled 15,926 transcripts, stratified into coding and non-coding, and validated our results by complementary mass spectrometry. A manual review of several gene loci, which are associated with cardiac function, corroborated the utility of our enhanced annotation. All our data are available for download and are provided as tracks for integration in genome browsers. We deem this resource as highly valuable for molecular research in an increasingly relevant large animal model.
Available online 10 October 2020
Gesehen am 01.03.2021